Self-Reflection in Teaching: Considerations on the Transformative Potential of Autoethnography - Luna, Diego; Pineda-Alfonso, José Antonio; García-Pérez, Francisco F.; Leal da Costa, Conceição (Pedagogika, 2023)
This paper explores the potential of autoethnography in teaching by developing a theoretical framework, presenting a case study, and discussing three alleged problems: excess subjectivism, observer bias, and lack of rigor. The described research experience shows that autoethnography functions as an element of ideological resistance, memory, and self-discovery in educational contexts.